An adiponectin receptor agonist antibody stimulates glucose uptake and fatty-acid oxidation by activating AMP-activated protein kinase. (February 2020) - Jung, Dokyung; Bucher, Felicitas; Ryu, Suyeon; Jeong, Jongwon; Lee, Beom Yong; Jeong, Youngtae; Kim, Minseok S.; Oh, Yong-Seok; Baek, Moon-Chang; Yoon, Jong Hyuk; Yea, Kyungmoo
Abstract: Adiponectin (Ad) is a representative adipocytokine that regulates energy homeostasis including glucose transport and lipid oxidation through activation of AMP-activated protein kinase (AMPK) pathways. Plasma levels of Ad are reduced in obesity, which contributes to type 2 diabetes. Therefore, agents that activate the Ad signaling pathway could ameliorate metabolic diseases such as type 2 diabetes. Here, we report the identification of a high-affinitive agonist antibody against Ad receptors. The antibody was selected by using phage display of human combinatorial antibody libraries. The selected antibody induced phosphorylation of the acetyl-CoA carboxylase (ACC) and AMPK in skeletal muscle cells and stimulated glucose uptake and fatty-acid oxidation (FAO) in myotubes. In addition, the antibody significantly lowered blood glucose levels during a glucose challenge in normal mice as well as basal blood glucose levels in a type 2 diabetic mouse model. Taken together, these results suggest that the agonist antibody could be a promising therapeutic agent for the treatment of metabolic syndrome such as type 2 diabetes.